2001
DOI: 10.1021/jo0103266
|View full text |Cite
|
Sign up to set email alerts
|

Phenol-Containing Macrocyclic Diamides as New Catalysts in the Highly Regioselective Conversion of Epoxides to β-Hydroxy Thiocyanates

Abstract: The regioselective ring-opening reactions of some epoxides with ammonium thiocyanate in the presence of a series of new phenol-containing macrocyclic diamides and also dibenzo-18-crown-6-, 18-crown-6-, benzo-15-crown-5-, and pyridine-containing macrocyclic diamide have been studied. The epoxides were subject to cleavage by NH(4)SCN in the presence of these catalysts under mild reaction conditions in various aprotic solvents. In this study, reagents and conditions have been discovered with which the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…13) The thiocyanohydrin intermediates of oxirane conversion with thiocyanate have been particularly difficult to isolate until recently where the regio and stereoselective synthesis and isolation of trans intermediate has been reported. [13][14][15][16] Additionally, a mixture of cis and trans thiocyanohydrin and 1,3-oxathiolan-2-imine intermediates was reported earlier from a steroid. 17) Compounds 3 and 4 represent the first regio and stereoselective synthesis and isolation of both intermedi-1120…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…13) The thiocyanohydrin intermediates of oxirane conversion with thiocyanate have been particularly difficult to isolate until recently where the regio and stereoselective synthesis and isolation of trans intermediate has been reported. [13][14][15][16] Additionally, a mixture of cis and trans thiocyanohydrin and 1,3-oxathiolan-2-imine intermediates was reported earlier from a steroid. 17) Compounds 3 and 4 represent the first regio and stereoselective synthesis and isolation of both intermedi-1120…”
Section: Resultsmentioning
confidence: 79%
“…13) Although the reaction mechanism was proposed in 1950's, the thiocyanohydrin intermediate was not isolated until recently. [13][14][15] Cyclic epoxides yield trans b-hydroxy thiocyanates under reasonably mild conditions and with proper catalyst. [14][15][16] These reactions are known to proceed with high regioselectivity, almost exclusively yielding anti-Markovnikov's products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 It is explained that the formation of thiiranes from the reaction of epoxides with thiocyanate ion has been occurred through the intermediacy of the corresponding β-hydroxy thiocyanates; however, this intermediate has not been isolated due to its rapid conversion to the corresponding thiirane. Literature review shows that hydroquinone, 4 HSCN, 5 DDQ, 6 Ti(O i Pr) 4 , 7 Ph 3 P(SCN) 2 , 8 TiCl 3 , 9 ZnCl 2 , 9 Pd(PPh 3 ) 4 , 10 TMSNCS/TBAF, 11 poly[N-(2-aminoethyl) acrylamido]trimethyl ammonium chloride (PTC), 12 GaCl3, 13 selectfluor, 14 metalloporphyrins, 15 dichloro(5,10,15,20-tetraphenylporphyrin) phosphorus (V) chloride [P(TPP)Cl 2 ]Cl, 16 tetraarylporphyrins, 17 PEG-SO3H, 18 thioxanthenone-fused azacrown ethers, 19 silica sulfuric acid, 20 Dowex-50X8, 21 2,6-bis[2-(o-aminophenoxy)methyl]-4-bromo-1-methoxybenzene (BABMB), 22 phenol-containing macrocyclic diamides, 23 2-phenyl-2-(2-pyridyl)imidazolidine (PPI), 24 B(HSO 4 ) 3 25 and Al(HSO 4 ) 3 /SiO 2 26 are the reagents which stabilize the produced β-hydroxy thiocyanate and therefore inhibit from the conversion to thiirane. In contrast to above mentioned protocols, it was also reported that conversion of epoxides to β-hydroxy thiocyanates can be achieved with high quantities of NH4SCN in the absence of any catalyst.…”
Section: Introductionmentioning
confidence: 99%